KONSEP KEBIJAKAN DAN KEBIJAKAN PENDIDIKAN - Widiatul Jannah, Nur; Jannah, Fitri; Adri, Riyan; Ananda, Rizki (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Education policy is important in the process of achieving national education goals. national education so that an understanding of the basic concepts of education policy is needed to produce proactive and problem-solving education policies. The purpose of writing this article is to examine the scope of education policy which consists of understanding the concept of education policy, characteristics of education policy, objectives of education policy, and functions of education policy. This writing methodology uses the literature study method. The writing of this article is done by reviewing several journals and books related to the concept of policy and education policy. The results of the study found that education policy is closely related to the field of education because the policy guides the development of the vision and mission of education to achieve academic goals through strategic implementation in the field of education. The characteristics of education policy are that it has educational objectives, fulfills legal-formal aspects, has operations, is made by the authorities, can be evaluated, and has a systematic approach. The approach to implementing education policy consists of an educational approach consisting of a structural approach, a procedural and managerial approach, a behavioral approach and a political approach.